嘉應學院客家研究院簡介 - 宋德劍; 冷劍波; De-jian Song; Jian-bo Leng (國立交通大學客家文化學院, 2015)
嘉應學院地處廣東省東北部具有「世界客都」之譽的梅州市，這裡是客家人的主要聚居地和客家文化的核心區，保存著豐富的客家人文資源，具有開展客家歷史文化研究得天獨厚的地緣優勢。嘉應學院依託客家文化的資源優勢，一直將客家研究與客家文化教育作為學校的主要辦學特色。本著服務地方的宗旨及配合梅州地方政府關於「文化梅州」的建設目標，2006年4月，嘉應學院與地方政府聯手整合全市資源和全校研究力量，在中國大陸率先成立了首個專職客家研究機構——客家研究院。

The Hakka Research Institute of Jiaying University was founded in 1990, it has become the center of Hakka studies in the world. Hakka Research Institute has made some achievements in the research of Hakka culture and Hakka cultural dissemination. The Hakka Research Institute is now based on "The Collaborative Innovation Centre of Guangdong and Taiwan's Hakka cultural heritage and development" is committed to Guangdong and Taiwan's Hakka culture research and innovation.
The Hakka Research Institute of Jiaying University
Keywords: 嘉應學院; 客家研究院; 粵臺客家文化; Jiaying University; The Hakka Research Institute; Hakka Culture of Guangdong and Taiwan